Analysis of Figurative Language Style in Chapter 1 of Stephenie Meyer's Twilight Novel - Rizka Fitri Silalahi; Nurfithri, Nurfithri (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This study examines the use of figurative language in Chapter 1 of Stephenie Meyer’s Twilight novel with a focus on its narrative functions and stylistic significance. Employing a descriptive qualitative approach, the data were collected through documentation by identifying and classifying sentences containing figurative language in the selected chapter. The analysis reveals that metaphor, personification, hyperbole, and simile are the dominant figurative forms used by the author. Among these, metaphor appears most frequently and plays a crucial role in representing the protagonist’s emotional state, psychological tension, and sense of alienation. Personification contributes to the vivid portrayal of setting and atmosphere, while hyperbole intensifies emotional expression and simile clarifies imagery through explicit comparison. The findings demonstrate that figurative language is strategically integrated into the narrative structure to enhance meaning, emotional depth, and reader engagement. This study highlights the importance of stylistic analysis in understanding literary texts and emphasizes the relevance of figurative language studies for both literary criticism and translation research, particularly in the context of contemporary popular novels.